Association of body composition and cardiovascular fitness with hypertension in a middle-aged adults: a cross-sectional study - Junga Lee; Jisuk Chae; Mihee Kim; Soo Young Jung; Seung Don Yoo; Si-Hyuck Kang; Kyesan Lee; Jung-Hyun Kim (Frontiers in Cardiovascular Medicine)
ObjectivesThis study aims to investigate the association between cardiovascular fitness, body composition (particularly abdominal obesity), and hypertension in middle-aged adults, considering the influence of factors such as age, gender, smoking status and alcohol status.MethodsA cross-sectional study was conducted among 60 healthy adults (mean aged 54.23 ± 7.34) recruited. Participants underwent assessments of anthropometry, body composition, blood pressure, and physical fitness. The primary outcome was the prevalence of hypertension. Secondary outcomes included body composition measures (body fat mass, body lean mass and waist circumference), and physical fitness assessments [grip strength, sit-ups, sit-and-reach test, and Young Men's Christian Association step (YMCA) test]. Participants with hypertension had significantly higher body fat mass and waist circumference compared to those without hypertension.ResultsThe risk of hypertension was significantly increased by 16.8% with a 1 kg increase in body fat and by 14.0% with a 1 cm increase in waist circumference. The risk of hypertension was significantly increased in the group with hypertension accompanied by abdominal obesity as cardiovascular fitness, measured by the YMCA step test, decreased (Adjusted OR: 0.339, 95% CI: 0.170–0.679).ConclusionThese findings highlight the significant association between abdominal obesity, reduced cardiovascular fitness, and hypertension in middle-aged Korean adults. Abdominal obesity and low cardiovascular fitness were identified as independent risk factors for hypertension in this population. These results suggest that weight management to reduce abdominal obesity and regular physical activity to promote cardiovascular fitness are key to the prevention and management of hypertension.